2018
DOI: 10.5539/jas.v10n12p92
|View full text |Cite
|
Sign up to set email alerts
|

Combining Ability and Heterosis for Agronomic and Yield Traits in Indica and Japonica Rice Crosses

Abstract: Understanding genetic variability and mode of gene action for agronomic and yield related traits is important in formulation of effective rice breeding program for genetic enhancement of grain yield. Combining ability analysis and heterosis was conducted to identify yield associated traits from nine male indicas and three female japonicas, together with their 27 F1 hybrids. Four parental lines, including Basmati 370, Basmati 217, K2-54 and Komboka showed good general combining ability in days to 50% flowering,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
4
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 15 publications
(36 reference statements)
6
4
1
Order By: Relevance
“…Analysis of the hybrids revealed that no specific combination obtained significant positive SCA values for all of the estimated traits simultaneously. This result is in agreement with those from previous studies in rice 14 , 16 , 18 , 23 , 25 as well as in maize 26 , bread wheat 27 . However, the crosses H1 [significant ( P < 0.01 ) for yield traits] and H7 [significant ( P < 0.01 ) for grain Fe and Zn content] showed positive SCA values for all the traits in irrigated method.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Analysis of the hybrids revealed that no specific combination obtained significant positive SCA values for all of the estimated traits simultaneously. This result is in agreement with those from previous studies in rice 14 , 16 , 18 , 23 , 25 as well as in maize 26 , bread wheat 27 . However, the crosses H1 [significant ( P < 0.01 ) for yield traits] and H7 [significant ( P < 0.01 ) for grain Fe and Zn content] showed positive SCA values for all the traits in irrigated method.…”
Section: Discussionsupporting
confidence: 94%
“…For TGW trait, the hybrid H1 had highest significant positive SCA effect in both the cultivation methods, in spite of both parents were with negative GCA effect. These observations are similar to the previous studies 16 18 , 23 , 25 . Generally, the hybrids with high SCA effects are recommended for heterosis breeding.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study for determining the best combiner among the lines and testers, positive and significant values were considered for all the traits except DFF, PH and NUFGPP. was identified to be the best combiner among the testers.These observations are in accordance with reports of [3,68,69], wherein no single parent was identified to have a good GCA for all the traits in their studies. [2]demonstrated that the most promising and high yielding hybrids in their study were produced from two of the parents which showed the best GCA for grain yield.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, in those cross combinations with higher and positive SCA values (due to high GCA values of parents), good combination of alleles from the parents might have resulted in positive SCA [2]. Also, those cross combinations that showed negative SCA effect value in our study, witnessed low to average GCA parental effects which is not in accordance with [68, 69]. The predicted genetic mechanisms of the SCA delineated in this study were in accordance with the report of [33].…”
Section: Discussioncontrasting
confidence: 60%
“…the other hand, the restorer Giza-182 was recorded as the best combiner for CHLC, PL, FP, 1000-GW, NPP, GY, and AH; additionally, it was a good combiner for GT (Table 3). These findings were better compared to previous reports that showed no single parental line was found to be the best or a good combiner for all yieldrelated characters [27][28][29]. Therefore, these studied parental lines can be used to improve grain yield and its component traits in hybrid-rice-breeding programs.…”
Section: Mean Performance and Combining Abilitymentioning
confidence: 47%